Hukum Islam (Antara kontinuitas dan Transformatif/perubahan) - Abduh Muhammad (Al-'Adl, 2008)
Islam is believed by its adherents as a religion that is absolutely true and universal, not limited by time and space and certain circumstances. This is as stated by the Qur'an itself, the teachings of Islam whose message is brought by Prophet Muhammad SAW is to all mankind wherever they are (kāffatan li al-nās, rahmatan li al-'Ālamīn). In contrast to earlier celestial religions, where the religions have limited capacity and time zone, which is temporary because it is limited by the presence of the next prophet and apostle, such as the teachings of Prophet Musa (AS) identified as Judaism, deadline- is the presence of the teachings of Prophet Isa AS identified as Christian or Christian religion. Similarly, the teachings of Prophet Isa AS this deadline is the presence of the teachings of the Prophet Muhammad SAW known as Islam, which is the ultimate of God's plan to provide guidance for mankind in carrying out their life management in the world, which later will be accountable to the hearing plenary of Allah in the Hereafter, because afterwards there is no more prophets and apostles who are sent by God for it. Thus, firmly that from the point of actualization, Islam does not have the dimension of space and time, so it is universal. Therefore, Islam should be acceptable to every human being on this earth, without having "conflict" with the condition and environment in which he is.As the last treatise of Allah SWT, Islam has been given attributes in it, namely the existence of elements tsabat (eternal, continuous, eternal) and at the same time is transformative. This means, that Islamic law as one dimension of Islamic teachings, of course, applies all the time. Therefore, he must be able to respond to the various problems of humanity that emerged after the apostles of the Prophet Muhammad SAW and so on until the end of time. This is an astonishing miracle of Islamic teachings, and as an indication of eternity, harmony, and integrity in every place and time.